Development and usability testing of an integrated geriatric care model (SMART system) to promote integrated home-based geriatric care - Rongrong Guo; Huan Fan; Shuqin Xiao; Ziling Zheng; Fangyu Yang; Yanyan Xiao; Xue Yang; Ying Wu (BMC Geriatrics)
Abstract Background Although integrated care has been proposed as a promising approach to the challenges of fragmented geriatric care, a universally accepted implementation framework for integrated care for older adults living at home remains elusive. This study aimed to address the gap by developing an integrated geriatric care model (SMART system) using a knowledge-based clinical decision support system (CDSS) architecture inspired by the principle of neural reflex and evaluate the usability of the SMART system. Methods The development of our SMART system was guided by the knowledge-based Clinical Decision Support System architecture and the principle of neural reflexes, which included 5 phases: (1) functional design; (2) architecture and database design; (3) security measures design; (4) user interface and visualization design; (5) prototypes development and iteratively testing. Subsequently, a cross-sectional study was conducted from December 2020 to February 2021, collecting older Chinese adults aged 60 years old and above consecutively to evaluate their usability perception of the Care Receiver App within the SMART system via the Health Information Technology Usability Evaluation Scale (Health-ITUES) version designed for older adults. Results The SMART system consisted of a Care Receiver App, a Professional Care Provider App, and a Cloud Platform. According to the assessment results and daily monitoring data, the SMART system can diagnose care problems and tailor interventions and implementation approaches to address the multifaceted care needs of older individuals. The personalized interventions and implementation approaches generated by the SMART system, after being reviewed and adjusted by professional geriatric nurses, will be sent to the corresponding care providers to facilitate coordinated care services. A total of 110 eligible older individuals were included in the usability testing. The Care Receiver App was perceived as useful and acceptable among older individuals with the mean scores for each item of the Health-ITUES version designed for older adults exceeding 3.00. Conclusions This study successfully developed an integrated geriatric care model using a knowledge-based CDSS architecture inspired by the principle of neural reflex. Furthermore, the study indicated acceptable usability perception of the SMART system among older population. Trial registration The study was registered in the Chinese Clinical Trial Registry (Registration number: ChiCTR-IOR-17010368) on 12/01/2017.